2017
DOI: 10.1371/journal.pone.0184950
|View full text |Cite
|
Sign up to set email alerts
|

The function of Drosophila larval class IV dendritic arborization sensory neurons in the larval-pupal transition is separable from their function in mechanical nociception responses

Abstract: The sensory and physiological inputs which govern the larval-pupal transition in Drosophila, and the neuronal circuity that integrates them, are complex. Previous work from our laboratory identified a dosage-sensitive genetic interaction between the genes encoding the Rho-GEF Trio and the zinc-finger transcription factor Sequoia that interfered with the larval-pupal transition. Specifically, we reported heterozygous mutations in sequoia (seq) dominantly exacerbated the trio mutant phenotype, and this seq-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this study, we identify them as direct sensors of arginine. Recent reports have described how levels of dietary amino acids affecting their dendritic branching ( Watanabe et al, 2017 ) and subsequently that nutrient-dependent changes in dendritic branching are distinct from their nociceptive function ( Brown et al, 2017 ), thus strengthening the role of multidendritic sensory neurons in nutrient-sensing. We have explored the response to dietary deprivation of amino acids using a semi-intact preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identify them as direct sensors of arginine. Recent reports have described how levels of dietary amino acids affecting their dendritic branching ( Watanabe et al, 2017 ) and subsequently that nutrient-dependent changes in dendritic branching are distinct from their nociceptive function ( Brown et al, 2017 ), thus strengthening the role of multidendritic sensory neurons in nutrient-sensing. We have explored the response to dietary deprivation of amino acids using a semi-intact preparation.…”
Section: Discussionmentioning
confidence: 99%
“…While we have hypothesized that NorpA is the major effector of Gαq in larval nociceptors, it is also possible that Gαq signals through other effectors aside from NorpA in the mdIV neurons. In some systems, the Trio rhoGEF is directly activated by Gαq signaling ( Lutz et al, 2005 ; Lutz et al, 2007 ; Rojas et al, 2007 ; Williams et al, 2007 ), and recent studies have demonstrated roles for Trio in regulating mdIV morphogenesis ( Brown et al, 2017 ; Iyer et al, 2012 ). However, Trio loss-of-function larvae do not display mechanical nociception defects, suggesting that Trio may not be an effector of Gαq for the modulation of nociceptor sensitivity ( Brown et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains puzzling why C4da dendrites undergo branch retraction in the L3 stage prior to the large-scale pruning in the pupal stage. As late L3 larvae advance to the wandering stage, they crawl out from food substrates to drier places for pupariation (Brown et al, 2017). C4da neurons are nociceptors for strong and harmful stimulations such as heat and UV light (Gorczyca et al, 2014;Xiang et al, 2010).…”
Section: Physiological Relevance Of Dendritic Pruning In Late Third-i...mentioning
confidence: 99%